Aksi Tanggap Pangan Korban Banjir Matang Seulimeng Melalui Dukungan Logistik Rumah Amal USK-UNG - Fachrul Akbar; Dian Permata Sari; Triami Lestari; Riska Amelia; Ummi Amanah; Darmansyah; Budi Mulyara; Ahyar Pulungan; Dian Asri; Febby Hadi Setyawan (Indo Publishing, 2026)
Flood disasters that struck Langsa City, particularly Matang Seulimeng Village, have led to a logistics crisis and the paralysis of economic activities for the affected communities. This Community Service (PKM) activity aims to provide rapid intervention through emergency food assistance to ensure the food security of residents during the emergency response period. This program was implemented through a strategic collaboration between Universitas Syiah Kuala (USK Charity House) and Universitas Negeri Gorontalo (UNG) as a tangible manifestation of the Tri Dharma of Higher Education. The methods employed include the preparation phase (data verification), the distribution phase (direct door-to-door delivery), and the evaluation phase. The results of the activity indicate that 20 packages of basic food assistance were successfully distributed to the 20 most affected households. This assistance proved capable of meeting the residents' basic nutritional needs during the flood isolation period while providing significant psychosocial support. The conclusion of this activity is that inter-university synergy is highly effective in accelerating humanitarian responses in disaster-prone areas. Suggestions for future activities include the need to develop a more integrated community-based disaster mitigation system to enhance the resilience of coastal communities in the future.